Aufwachsen in schwieriger Zeit: Kinder in Gemeinde und Gesellschaft (Gütersloher Verl.-Haus, 1995)
1. Dtn 05:01-03 - Hertzsch, Klaus-Peter (Bibelarbeit), 2. Röm 08:01-17 - Steffensky, Fulbert (Bibelarbeit)